Kewenangan Lurah Surabaya dalam Penerbitan Surat Ahli Waris menurut UU Pelayanan Publik - Jussaq Noor Hamdhani; Karim Karim (Pusat Riset dan Inovasi Nasional, 2024)
Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency No. 3 of 1997 states that Indonesians of native descent may obtain a Certificate of Heirship at the sub-district level, witnessed by the sub-district head, village head, and two witnesses. However, the regulation lacks clarity on the exact authority of village heads and technical procedures involved in issuing these certificates. This ambiguity creates legal uncertainty and concern for village heads, particularly in Surabaya, where they play a key role in frontline public services. In response, the Surabaya City Government regularly reformulates mayoral regulations to strengthen sub-district and village performance in administering heirship services. This study uses a normative juridical method with statutory and conceptual approaches. Findings show that several regulations govern village head authority in heirship matters, including Ministerial Regulation No. 3/1997 and Surabaya Mayor Regulations No. 75/2018, No. 63/2019, No. 50/2021, and No. 3/2022. These largely align with public service principles in Law No. 25/2009. To further enhance village service quality, ongoing legal reform should focus on strengthening principles such as legal certainty, professionalism, non-discrimination, accountability, and accessibility—ensuring equitable and timely services, especially for vulnerable groups.